Opportunities and pitfalls in (sub)diffuse reflectance spectroscopy - Witteveen, Mark; Faber, Dirk J.; Sterenborg, Henricus J. C. M.; Ruers, Theo J. M.; van Leeuwen, Ton G.; Post, Anouk L. (Frontiers in Photonics, 2022)
For a long time, steady-state reflectance spectroscopy measurements have been performed so that diffusion theory could be used to extract tissue optical properties from the reflectance. The development of subdiffuse techniques, such as Single Fiber Reflectance Spectroscopy and subdiffuse SFDI, provides new opportunities for clinical applications since they have the key advantage that they are much more sensitive to the details of the tissue scattering phase function in comparison to diffuse techniques. Since the scattering phase function is related to the subcellular structure of tissue, subdiffuse measurements have the potential to provide a powerful contrast between healthy and diseased tissue. In the subdiffuse regime, the interrogated tissue volumes are much smaller than in the diffuse regime. Whether a measurement falls within the diffuse or subdiffuse regime depends on tissue optical properties and the distance between the source and detector fiber for fiber-optic techniques or the projected spatial frequency for hyperspectral imaging and SFDI. Thus, the distance between source and detector fibers or the projected spatial frequency has important implications for clinical applications of reflectance spectroscopy and should be carefully selected, since it influences which tissue optical properties the technique is sensitive to and the size of the tissue volume that is interrogated. In this paper, we will review the opportunities and pitfalls in steady-state reflectance spectroscopy in the subdiffuse and the diffuse regime. The discussed opportunities can guide the choice of either the diffuse or subdiffuse regime for a clinical application, and the discussed pitfalls can ensure these are avoided to enable the development of robust diagnostic algorithms. We will first discuss the relevant basics of light-tissue interaction. Next, we will review all the tissue scattering phase functions that have been measured and investigate which scattering phase function models are representative of tissue. Subsequently, we will discuss the sensitivity of diffuse and subdiffuse techniques to tissue optical properties and we will explore the difference in the interrogation depth probed by diffuse and subdiffuse techniques.